2016
DOI: 10.1016/j.jembe.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Routine metabolic rates of pelagic marine fishes and cephalopods as a function of body mass, habitat temperature and habitat depth

Abstract: Routine metabolic rates of pelagic marine fishes and cephalopods as a function of body mass, habitat temperature and habitat depth Tsutomu Ikeda 16-3-1001 Toyokawa-cho, Hakodate 040-0065, Japan a b s t r a c t Cephalopods and fishes are major components of marine micronekton and nekton, so an understanding of their physiology and roles in ocean biogeochemistry is important. I compiled the routine respiration rates (50 datasets on 41 cephalopod species; 102 datasets on 90 fish species) from various depth horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 76 publications
1
31
1
Order By: Relevance
“…The average RMR of P. stellatus in our study was 134.04 mg O 2 hr −1 kg −1 ; comparable to those found across fish taxa (Bond, 2007;Ikeda, 2016), but relatively high compared to reports from other flatfishes (Duthie, 1982;Priede & Holliday, 1980). One explanation is that our flounder were juveniles, all 16.0 cm SL or less, while flatfish used in these other studies were adults of ~30.0 cm SL.…”
Section: Discussionsupporting
confidence: 88%
“…The average RMR of P. stellatus in our study was 134.04 mg O 2 hr −1 kg −1 ; comparable to those found across fish taxa (Bond, 2007;Ikeda, 2016), but relatively high compared to reports from other flatfishes (Duthie, 1982;Priede & Holliday, 1980). One explanation is that our flounder were juveniles, all 16.0 cm SL or less, while flatfish used in these other studies were adults of ~30.0 cm SL.…”
Section: Discussionsupporting
confidence: 88%
“…The O:N ratios observed here were higher than is typical for squid (11-17), which have a well-known protein-rich diet (Ikeda, 2016). One animal was fasted for 3 days and had a notably higher O:N ratio than any other individual, suggesting a use of lipid reserves.…”
Section: Discussioncontrasting
confidence: 49%
“…Contrary to Hidaka et al (2001), we found that mesozooplankton contributed more to downward carbon export than micronekton in the B-CCE and WCE, while only micronekton were contributing to export in the R-WCE. This difference was primarily driven by the higher metabolic rates, and thus respiratory flux, of mesozooplankton when compared to micronekton (Ikeda, 1985(Ikeda, , 2016. However, our sampling was concentrated in eddy centers, so it is possible that we missed the portion of micronekton that is thought to aggregate at eddy peripheries (Sabarros et al, 2009;Drazen et al, 2011).…”
Section: Vertical Migration and Active Carbon Transportmentioning
confidence: 99%
“…The uncertainty associated with the models may indeed plague such estimates. Respiration was estimated using empirical allometric relationships dependent on carbon weight and in situ temperature from the literature (Ikeda, 2013b(Ikeda, , 2014(Ikeda, , 2016Henschke et al, 2019). For all relationships used, temperature and weight explained >86% of the variation in oxygen uptake, suggesting minimal uncertainty with the models.…”
Section: Uncertainty and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation